(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Dentistry is a most stressful profession in the medical field. During the practicum period, most of the dental students feel stressed from internal and external environmental stressors. Therefore, this study was designed to assess the stress among dental students, this will provide applicable insights for further improvement. MATERIALS AND METHODS: A descriptive, cross-sectional research design was used with an online Structure questionnaire to assess stress among the students of dental colleges of Nepal by using dental environmental stress (DES) questionnaire, which was developed by Garbee et al. Probability Proportionate to the size sampling technique was used to collect the sample. The organized data will be entered by using IBM Statistical Package for Social Science (SPSS) version 20.0. The data will be further analyzed by using descriptive statistics (frequency, percentage, mean, median and standard deviation) and inferential statistics. RESULTS: Out of 756 students, 58.7% of the respondents were equal to or greater than 22 years of age. The median age was 22 years. Among them, 78.7% were female. Stress-related to domain, Professional and carrier-related stressor had higher, followed by academic performance and Clinic patient-related stress is mean percentage was 70.43, 69.17 and 61.09, respectively. About 50.3% had moderate levels and 15.3% of respondents had a severe level of stress. There was statically association between stress level with age (p=0.01), first choice of study (p=0.026), academic year (p=<0.001) and current residence (p=<0.001). CONCLUSIONS: Professional and carrier-related stressor, academic-related and patient-related stressors are higher in dental students. Severe Levels of stress increased over the academic year and peaked in 5th year. Stress affects student academic as well as professional carrier in the future so minimize the stressor by the institutional level.